Factors Influencing the Implementation of Integrated Financial Management Information Systems: Study Focus on Bangladesh - Noor , Md Asad (South Asian Journal of Social Sciences and Humanities, 2022)
Background of the study: Integrated Financial Management Information Systems (IFMIS) can help improve public sector management by giving managers real-time financial data to make better decisions. The Bangladeshi Public Service is currently busy with the implementation of an IFMIS. However, implementing IFMIS such a project has proved to be a demanding undertaking and has not been met with resounding success. Objectives of the research: The research is primarily focused to identify the factors influencing the implementation of IFMIS in Bangladesh. Along aside, this paper assesses the influence of technical capacity of staff on implementation of IFMIS in Bangladesh’s public institutions and staff resistance on the deployment of IFMIS. Methodology of the research: The paper draws from two theories in investigating the issues of IFMIS adoption for public financial management. The theories include System Theory and Rodger’s Theory. A simple Random sampling technique is used to collect the information from targeted respondents with a structured questionnaire. Around 80 respondents were selectively targeted. Findings of the research: One of the Major findings of the study is that the governments have a strategic plan that recognizes political, administrative, and capacity limits that were found to be supported by respondents. The study indicates that the government has revised the wage structure to compete with the private sector and to prevent skilled employee turnover. Research shows that employees have the necessary skills and credentials to implement IFMIS. Furthermore, the study looked at how IFMIS deployment is affected by capacity and abilities. Contributions of the research: The results revealed a significant connection between capacity and skills and IFMIS deployment. However, it is found that the infrastructure is central concern for successful IFMIS implementation. Moreover, the government's interaction with the external consultants is seen to be indecisive. Finally, the study recommends that government should uphold the strategic plan that identifies all the constraints and should have detail plan for maintaining its education system's alignment with information technology.
Keywords: Bangladesh; Integrated Financial Systems; Management Information Systems; Roger’s Theory; System Theory